2017
DOI: 10.18632/oncotarget.17734
|View full text |Cite
|
Sign up to set email alerts
|

Succinate: An initiator in tumorigenesis and progression

Abstract: As an intermediate metabolite of the tricarboxylic acid cycle in mitochondria, succinate is widely investigated for its role in metabolism. In recent years, an increasing number of studies have concentrated on the unanticipated role of succinate outside metabolism, acting as, for instance, an inflammatory signal or a carcinogenic initiator. Actually, succinate dehydrogenase gene mutations and abnormal succinate accumulation have been observed in a battery of hereditary and sporadic malignancies. In this review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
83
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(87 citation statements)
references
References 94 publications
4
83
0
Order By: Relevance
“…A better understanding of these “metabolic synapses” between tumor and other (stromal) cells will be a great challenge over the next few years and molecular imaging is ideally placed to play a central role in this regard. Interestingly, a recent study has shown that succinate has pro-angiogenic functions (chemotactic motility, tube-like structure formation and proliferation) and also upregulates vascular endothelial growth factor expression [67, 81]. This concept also supports a notion that succinate may contribute to the aggressive behavior potential of SDHx tumors through the new concept outlined here and in our previous publication, affecting various stromal cells and ultimately promoting metastasis.…”
Section: Future Perspectivessupporting
confidence: 77%
“…A better understanding of these “metabolic synapses” between tumor and other (stromal) cells will be a great challenge over the next few years and molecular imaging is ideally placed to play a central role in this regard. Interestingly, a recent study has shown that succinate has pro-angiogenic functions (chemotactic motility, tube-like structure formation and proliferation) and also upregulates vascular endothelial growth factor expression [67, 81]. This concept also supports a notion that succinate may contribute to the aggressive behavior potential of SDHx tumors through the new concept outlined here and in our previous publication, affecting various stromal cells and ultimately promoting metastasis.…”
Section: Future Perspectivessupporting
confidence: 77%
“…Several studies have demonstrated that elevated concentrations of succinate may induce metabolic reprogramming of the tumour microenvironment to promote cancer cell growth. Furthermore, succinate can promote a state of pseudohypoxia, a common condition in advanced tumours where, despite normal oxygen levels, gene expression is regulated by hypoxia‐inducible factor 1 (HIF‐1), which induces genes involved in glycolysis, angiogenesis, and EMT (Zhao, Mu, & You, ). Succinate is also involved in the metabolism of other metabolites and in the γ‐aminobutyric acid (GABA) shunt, which consists of a cycle of reactions ensuring the production and conservation of GABA.…”
Section: Oncometabolites and Their Related Metabolic Enzymesmentioning
confidence: 99%
“…Using rodent models, SUCNR1 signalling has been implicated in several diseases, including rheumatoid arthritis (Littlewood‐Evans et al , ), hypertension, diabetes, metabolic syndrome, ischemia/reperfusion injury, and cancer (Gilissen et al , ). Succinate is also considered an oncometabolite for its effects on reactive oxygen species (ROS) production (Tretter et al , ; Zhao et al , ), angiogenesis (Mu et al , ; Zhao et al , ), stem cell migration (Ko et al , ), and EMT (Aspuria et al , ).…”
Section: Oncometabolites and Their Related Metabolic Enzymesmentioning
confidence: 99%
“…Protein lysine residues can be subjected to various PTMs, including acetylation, propionylation, methylation, butyrylation, succinylation, crotonylation, malonylation, glutarylation, long‐chain fatty acylation, ubiquitylation and 2‐hydroxysobuturylation . Previously, we demonstrated that succinate acts as an oncometabolite and functions as an initiator in tumourigenesis and tumour progression . Moreover, protein lysine succinylation has been identified as a frequently occurring PTM that plays an important role in regulating heart metabolism and cardiac function .…”
Section: Introductionmentioning
confidence: 99%